Pengembangan Media Pembelajaran Roda Putar Rangsa Dalam Pembelajaran IPS Pada Siswa Kelas IV Sekolah Dasar - Masyithah, Almarhia; Hakim, Lukman; Aryaningrum , Kiki (CV. ITTC INDONESIA, 2024)
This research is entitled Development of Rangsa Spin Wheel Media in Social Studies Learning for Class IV Elementary School Students. The aim of this research is to develop a product in the form of Rangsa spin wheel learning media in social studies learning for Class IV elementary school students. To determine the effectiveness and practicality of developing learning media. Rangsa spinning wheel in social studies learning for fourth grade elementary school students. This research adopts the Research and Development type of research using Analysis, Design, Development and Implementation. The results of this research are based on research conducted on the development of the Rangsa Spin Wheel Media with the help of the Canva Application in Social Sciences Subjects for Class V students of SDN 96 Palembang, it can be concluded that the media was developed using the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model and was rated